Indonesian Cultural Diplomacy: The Role of Indonesian Schools in Saudi Arabia - Zuhri, Anis Fuadah; Sholeh, Badrus (International Journal of Basic Educational Research, 2024)
This study delves into the intricate dynamics of cultural diplomacy and nationalism as orchestrated by Indonesian Schools in Riyadh, Saudi Arabia, emphasizing the strategic role of performance arts in fostering international relations and national identity. The research aims to elucidate the involvement of students and teachers from the Indonesian School of Riyadh in cultural performances, delineating its significance in the broader context of Indonesia's diplomatic outreach in Saudi Arabia. Adopting a qualitative methodology, the investigation centered on interviews with twenty teachers who participated in cultural events in Riyadh from 2022 to 2023. These interviews, conducted via Google Forms, illuminated the proactive engagement of the Indonesian educational community in cultural diplomacy through music, dance, and cultural festivals. The findings highlight that these cultural performances serve not only as a medium of cultural expression but also as a pivotal mechanism in reinforcing the diplomatic ties between Indonesia and Saudi Arabia. Furthermore, the study reveals that these activities are instrumental in instilling a sense of nationalism among Indonesian students abroad, providing them with a tangible connection to their cultural heritage. The performances have been strategically employed to showcase Indonesia’s rich cultural tapestry, thereby facilitating a deeper cultural understanding and appreciation among the Saudi populace and international community in Riyadh. The research acknowledges the limitation of its sample size and calls for broader studies to assess the long-term impact of cultural performances on diplomatic relations and national identity construction. In conclusion, the study posits that cultural diplomacy through educational institutions like the Indonesian School of Riyadh has emerged as an effective tool in the post-Vision 2030 diplomatic landscape of Saudi Arabia, suggesting a transformative shift towards more culturally nuanced diplomatic engagements.